Evaluation of a web-based information platform on youth depression and mental health in parents of adolescents with a history of depression - Lucia Iglhaut; Regine Primbs; Sara Kaubisch; Chiara Koppenhöfer; Charlotte E. Piechaczek; Pia-Marie Keim; Maria Kloek; Lisa Feldmann; Gerd Schulte-Körne; Ellen Greimel (BMC, 2024)
Abstract Research shows the important role of parents' mental health literacy in detecting depressive symptoms and supporting their children to seek professional help. Improving mental health literacy in parents has recently gained even greater importance due to the negative impact of the COVID-19 pandemic on children and adolescents' mental health. The aim of the present experimental pre-post-follow-up study was to examine knowledge change after the reception of contents from an innovative web-based platform ( www.ich-bin-alles.de/eltern ) containing evidence-based information on youth depression and mental health in parents of adolescents with a history of depression. A second aim was to assess evaluation of the layout and the acceptance of the platform. N = 33 parents of adolescents with a history of depression (either current or remitted depression) were presented different content domains of the website. Participants' knowledge about depression was assessed at pre- and post-intervention, and at a four week follow-up. Moreover, parents evaluated the acceptance and the layout of the website. The trial was preregistered at clinicaltrials.gov (NCT05335564). The results showed a significant increase in total knowledge from pre to post, which remained stable over the course of four weeks. Explorative analyses showed that sociodemographic variables did not influence the extent of knowledge gain. Acceptance rates were high and evaluations of the website's layout were positive. The findings show that the web-based information portal is a promising and appealing means to increase parental knowledge on youth depression. Low-threshold psychoeducational approaches like websites are particularly relevant in times of crisis and increased prevalence rates of depressive symptoms and disorders (ehealth). These results are an important basis for future studies as well as approaches that aim to impart knowledge about mental disorders like youth depression via web-based means. Furthermore, they bear implications for policy decisions concerning mental health education and campaigns.